Feed gap assessment in Tanzania Southern Highlands through Improved Forages And Feeding Strategies Project - Paul, Birthe K.; Nzolega, Beatus; Buyegi, George (International Center for Tropical Agriculture, 2020)
Feedgap assessment aims to collect empirical data on feeding quantities and practices in Tanzania. It is standard data collection tool (Excel) has been previously developed for Tanzania, and adjusted after a workshop with TALIRI and CIAT. It is constituted of empirical feed and milk measurements and labour observations, feed sub-sampling, as well as questions to the household member in charge of cattle management. (2020-02-27)